2009
DOI: 10.1111/j.1750-3841.2009.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Infrared Heating on the Formation of Sesamol and Quality of Defatted Flours from Sesamum indicum L.

Abstract: Infrared (IR) heating offers several advantages over conventional heating in terms of heat transfer efficiency, compactness of equipment, and quality of the products. Roasting of sesame seeds degrades the lignan sesamolin to sesamol, which increases the oxidative stability of sesame oil synergistically with tocopherols. IR (near infrared, 1.1 to 1.3 microm, 6 kW power) roasting conditions were optimized for the conversion of sesamolin to sesamol. The resultant oil was evaluated for sesamol and tocopherol conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Minute amounts of the enterolignans enterodiol and enterolactone are sometimes found in animal foods (milk products) as a result of their production by bacterial metabolism in the animals' guts, but these are exceptions 36–39 . Little has been done to investigate the effects of storage and processing on lignans in most foods, 29–32,40–45 although it is known that the lignan content is apparently not changed considerably during the processing of flaxseed 46–50 and sesame seed 51–59 …”
Section: Food Sources Of Lignansmentioning
confidence: 99%
“…Minute amounts of the enterolignans enterodiol and enterolactone are sometimes found in animal foods (milk products) as a result of their production by bacterial metabolism in the animals' guts, but these are exceptions 36–39 . Little has been done to investigate the effects of storage and processing on lignans in most foods, 29–32,40–45 although it is known that the lignan content is apparently not changed considerably during the processing of flaxseed 46–50 and sesame seed 51–59 …”
Section: Food Sources Of Lignansmentioning
confidence: 99%
“…At present, IR has been utilized to roast seeds and leads to positive results in some studies. Kumar et al reported that better quality was found in peanuts roasted by IR compared to conventional heating methods; increased oxidative stability was observed in sesame oil extracted from Near‐IR roasted sesame seeds. Lee et al roasted peanuts hulls and found higher amount of phenolics in Far‐IR roasted samples compared to heat‐treated ones.…”
Section: Introductionmentioning
confidence: 99%
“…Sesaminol is a naturally occurring trace compound in sesame seed and its crude oil. It is formed from sesamolin during sesame seed roasting 6, 7 and heating or refining operations (i.e., acid‐activated clay bleaching) 8–10. Among the lignans from sesame seeds, sesaminol, and its isomers were shown to have the most potent antioxidative activity in vitro experimental system, having higher antioxidative activity than α‐tocopherol and BHT 11.…”
Section: Introductionmentioning
confidence: 99%